Successful implementation of best medical treatment for patients with asymptomatic carotid artery stenosis within a randomized controlled trial (SPACE-2) - Reiff, Tilman; Eckstein, Hans-Henning; Mansmann, Ulrich; Jansen, Olav; Fraedrich, Gustav; Mudra, Harald; Hacke, Werner; Ringleb, Peter A. (Neurological research and practice, 2021)
BACKGROUND: Asymptomatic carotid artery stenosis (ACS) can be treated with carotid endarterectomy (CEA), carotid artery stenting (CAS), or best medical treatment (BMT) only. For all treatment options, optimization of vascular risk factors such as arterial hypertension, hyperlipidemia, smoking, obesity, and insufficient physical activity is essential. Data on adherence to BMT and lifestyle modification in patients with ACS are sparse. The subject of this investigation is the implementation and quality of risk factor adjustment in the context of a randomized controlled trial. METHODS: A total of 513 patients in the prematurely terminated, randomized, controlled, multicenter SPACE-2 trial (ISRCTN 78592017) were analyzed within one year after randomization into 3 groups (CEA, CAS, and BMT only) for implementation of prespecified BMT recommendations and lifestyle modifications. Measurement time points were the screening visit and visits after one month (D30), 6 months (M6), and one year (A1). Differences between groups and follow-up visits (FUVs) relative to the screening visit were investigated. FINDINGS: For all FUVs, a significant increase in statin medication (91% at A1; p < 0.0001) was demonstrated to be associated with a significant decrease (p < 0.01) in cholesterol levels (median 167 mg/dl at A1) and LDL cholesterol levels (median 93 mg/dl at A1). The lowest cholesterol levels were achieved by patients in the BMT group. Seventy-eight percent of all patients reached predefined target cholesterol levels (< 200 mg/dl), with significantly better rates in the BMT group (p = 0.036 at D30). Furthermore, a significant decrease in arterial blood pressure at all FUVs (p < 0.05) was associated with a significant increase in antihypertensive medication (96% at A1, p < 0.0001). However, only 28% of patients achieved the predefined treatment goal of a systolic blood pressure of ≤ 130 mmHg. Forty-two of a total of 100 smokers at the screening visit quit smoking within one year, resulting in a significant increase in nonsmokers at all FUVs (p < 0.0001). Recommended HbA1c levels (< 7%) were achieved in 82% without significant changes after one year. Only 7% of obese (BMI > 25) patients achieved sufficient weight reduction after one year without significant changes at all FUVs (median BMI 27 at A1; p = 0.1201). The BMT group showed significantly (p = 0.024) higher rates of adequate physical activity than the intervention groups. Furthermore, after one year, the BMT group showed a comparatively significantly better implementation of risk factor modification (77%; p = 0.027) according to the treating physician. INTERPRETATION: SPACE-2 demonstrated sustained improvement in the noninterventional management of vascular risk factors in patients treated in a clinical trial by general practitioners, internists and neurologists. The best implemented treatment targets were a reduction in cholesterol and HbA1c levels. In this context, a significant increase in statin use was demonstrated. Blood pressure control missed its target but was significantly reduced by intensification of antihypertensive medication. Patients on BMT only had better adjusted lipid parameters and were more physically active. However, all groups failed to achieve sufficient weight reduction. Due to insufficient patient recruitment, the results must be interpreted cautiously. TRIAL REGISTRATION: ISRCTN Registry, ISRCTN78592017, Registered 16 June 2007, https://www.isrctn.com/search?q=78592017 .
Gesehen am 10.11.2021